THE POWER OF STORY-BASED LEARNING IN ENGLISH LITERACY DEVELOPMENT: THE INTERPLAY OF TEACHER-STUDENT READINESS AND PARENT INVOLVEMENT - Ratminingsih, Ni Made; Santosa, Made Hery; Ana, I Ketut Trika Adi; Agustina, Noni (LLT Journal: A Journal on Language and Language Teaching, 2025)
While literacy serves as the foundation of language proficiency and a key predictor of academic success, its development depends on teacher and student readiness, parent involvement, and effective use of media such as stories. Previous studies show that story-based learning enhances comprehension and supports early reading, especially when sustained collaboration between teachers and parents is present. Due to the growing emphasis on early literacy and the integration of stories in language education, this study investigates the underexplored factors of teacher readiness, student readiness, and parent involvement in ensuring effective literacy development for young learners. The researchers employed a descriptive-quantitative research design using a survey. This study involved seven teachers, 202 students, and 124 parents as participants. Three questionnaires were used as the primary instruments to collect data. The data were analyzed descriptively using statistical descriptive analysis. The findings revealed that teacher readiness was very high, whereas students’ readiness and parents’ involvement were high for enhancing learner’s literacy development through story-based learning. Thus, it is concluded that the teachers have satisfying readiness, while the learners and parents hold high readiness and involvement that support literacy success. These results imply that all parties should work collaboratively to build young learners’ literacy skills, which are vital for academic accomplishment.